2017
DOI: 10.1038/s41598-017-04170-1
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced antiviral and antifibrotic effects of short hairpin RNAs targeting HBV and TGF-β in HBV-persistent mice

Abstract: The hepatitis B virus (HBV) causes acute and chronic liver infection, which may lead to liver cirrhosis and hepatocellular carcinoma. Current treatments including interferons and nucleotide analogs, have limited therapeutic effects, underscoring the need to identify effective therapeutic options to inhibit HBV replication and prevent complications. Previous animal models mimicking chronic HBV infection do not faithfully reflect disease progression in humans. Here, we used our established HBV-persistent mouse l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…These results suggested that AAVshRNA treatment inhibited lipogenesis and improved lipid metabolism. Hepatocyte steatosis was observed in HBV(+) mice, consistent with our previous study [77], and was alleviated after AAVshRNA treatment [44]. These findings suggested that AAVshRNA alleviated hepatocyte steatosis and liver fibrosis by decreasing hepatocyte fatty acid uptake and de novo lipogenesis via attenuation of FABP1 and ME1 expression.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…These results suggested that AAVshRNA treatment inhibited lipogenesis and improved lipid metabolism. Hepatocyte steatosis was observed in HBV(+) mice, consistent with our previous study [77], and was alleviated after AAVshRNA treatment [44]. These findings suggested that AAVshRNA alleviated hepatocyte steatosis and liver fibrosis by decreasing hepatocyte fatty acid uptake and de novo lipogenesis via attenuation of FABP1 and ME1 expression.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, it is necessary to elucidate the mechanisms of hepatic fibrosis and develop new medicines for blocking and reversing hepatic fibrosis. Our previous study showed that AAVshRNA had anti-hepatic fibrosis effects in HBV-replicated mice with liver fibrosis [44]. Moreover, fibrotic markers, including α-SMA, collagen I, and collagen III, were significantly reduced.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations